2016
DOI: 10.1093/ntr/ntw212
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Behaviors and Beliefs in Persons Living With Hepatitis C

Abstract: This is the first paper to examine, in detail, sociobehavioral correlates of tobacco use in PLHC. PLHC are recognized by the Department of Health and Human Services as a high-priority health disparities population. We are not aware of any tobacco treatment services designed specifically for PLHC. The first step in designing an intervention is defining the characteristics of the target group. Our findings will begin to address this need, and may prove useful in optimizing tobacco treatment strategies for smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The national sample described herein and one earlier paper reporting on a small cohort from the Bronx, New York 32 indicate that hepatitis C+ smokers possess various characteristics that may interfere with successful quitting. Black race, low socioeconomic status, lower educational attainment, psychiatric illness, and comorbid substance use are all associated with lower cessation rates, and these factors also suggest the need for intensive tobacco treatment rather than brief interventions.…”
Section: Discussionmentioning
confidence: 61%
“…The national sample described herein and one earlier paper reporting on a small cohort from the Bronx, New York 32 indicate that hepatitis C+ smokers possess various characteristics that may interfere with successful quitting. Black race, low socioeconomic status, lower educational attainment, psychiatric illness, and comorbid substance use are all associated with lower cessation rates, and these factors also suggest the need for intensive tobacco treatment rather than brief interventions.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, very little research has explored correlates of cigarette smoking among people with HCV. These available studies have identified older age, alcohol use, use of illicit substances, and experiencing pain [15,16] as correlates of cigarette smoking among HCV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, researches indicated that hypertension, heart failure and diabetes were the most common comorbidities of chronic obstructive pulmonary disease, importantly, the incidence of patients with at least one comorbidity was 84.5% [7]. Furthermore, researchers indicated that there is a correlation between smoking and hepatitis C virus infection in the United States [8]. For infectious diseases, chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) are a major global health burden, which usually results in liver cirrhosis and hepatocellular carcinoma (HCC) [9–11].…”
Section: Introductionmentioning
confidence: 99%